Mechanical Engineering and Applied Mechanics : Selected, Peer Reviewed Papers from the 13th Indonesia Conference of Mechanical Engineering, October 15-16, 2014, Depok, Indonesia - Supriadi, Sugeng (Applied mechanics and materials ;, 2015)
These are the proceedings of the 13th Indonesia Conference on Mechanical Engineering hosted by Universitas Indonesia (Jakarta, Indonesia) on October 15-16, 2014. The conference covers topics of fields applied mechanics, mechanical materials processing, dymanics, mechanical engineering. Among the submitted papers, conference committee selects 27 papers to be published in this collection covering current knowledge in material science and applied mechanics.